APLIKASI PENJUALAN BATIK JAMBI FARAS BERBASIS WEB: Applications;E-commerce;Internet;Sales;Web. - Pariyadi; Aminuddin, Fattachul Huda; Afrilianto, Robby (JURNAL AKADEMIKA, 2021)
Jambi Faras Batik Shop is a business engaged in the sale of Jambi batik clothes. Currently, Jambi Faras Batik Shop wants to increase its sales level by expanding its sales outside the city of Jambi to seek greater sales profits. The purpose of this research is to build a web-based computerized sales application that includes product catalogs, sales transactions, and reports that are expected to increase batik sales turnover. This application is built using the PHP programming language and MySQL database. The input to this application is in the form of admin data, item data, sales data, and customer data. Process data in this application are in the form of admin data processing, goods data processing, sales data processing, and customer data processing. The output of this application is a sales report. The results of this study are in the form of a web-based sales application that can help Jambi Faras Batik Stores in marketing merchandise with a wider range and make it easier to make sales reports.